Facilitated Communication: The Resurgence of a Disproven Treatment for Individuals With Autism. (September 2018) - Ganz, Jennifer B.; Katsiyannis, Antonis; Morin, Kristi L.
Purveyors of false treatments frequently claim their treatments are effective, despite a lack of evidence. In some cases, these treatments can lead to dire results. This column examines the use of one such false treatment, facilitated communication, that has reemerged despite a substantial body of evidence discrediting it. A description of the technique is provided along with a summary of the research that disproves facilitated communication. Legal issues related to the use of facilitated communication in school settings are outlined along with recommendations for critically evaluating any potential intervention or treatment.